High-intensity demands of 6-a-side small-sided games and 11-a-side matches in youth soccer players - Goto, H.; King, J. A. (Pediatric Exercise Science, 2019)
The purposes of the present study were to examine high-intensity running distance during 6-a-side small-sided games (SSGs) and 11-a-side matches (11M) in youth soccer players using speed and metabolic power approaches and the magnitude of difference between the high-intensity running distance calculated with the 2 approaches. Method: A total of 11 outfield players (age=16.3 [0.6] y) performed SSGs with 3 pitch sizes (small SSG [SSGS], medium SSG, and large SSG [SSGL]) and 11M. A Global Positioning System (15 Hz) was employed to calculate total distance covered, distance covered at a speed =4.3 m·s-1 (TS), and metabolic power of =20 W·kg-1 (TP). Results: The total distance covered increased from SSGS through to SSGL (P<.001) and was greater during 11M and SSGL compared with other SSGs (P<.01). TS and TP increased from SSGS (TS vs TP=98 [55] vs 547 [181] m) through to SSGL (538 [167] vs 1050 [234] m; P<.001). TS and TP during 11M (370 [122] vs 869 [233] m) was greater than SSGS (P<.001 for both) and less than SSGL (P<.05 for both). The magnitude of difference between TS and TP (as a percentage) was lower with an increase in pitch size during SSGs and was greater in SSGS (615% [404%]; P<.001), medium SSG (195% [76%]; P<.05), and smaller in SSGL (102% [33%]; P<.01) compared with 11M (145% [53%]). Conclusion: SSGs can replicate the high-intensity demands of 11M and the speed approach underestimates the high-intensity demands of SSGs and 11M compared with the metabolic power approach.